Given the population model by the following linear first order PDE in $u(a,t)$ with constants $b$ and $\mu$ :

$$u_a + u_t = -\mu t u\,\,\,\,\,a,t>0$$


$$u(0,t)=F(t)=b\int_0^\infty u(a,t)\,\mathrm{d}a$$

We can split the integral in two with our non-local boundary data:

$$F(t)=b\int_0^t u(a,t)\,\mathrm{d}a+b\int_t^\infty u(a,t)\,\mathrm{d}a$$

Choosing the characteristic coordinates $(\xi, \tau)$ and re-arranging the expression to form the normal to the solution surface we have the following equation with initial conditions:

$$\bigl(u_a, u_t, -1\bigr) \bullet \bigl(1, 1, -\mu t u \bigr)=0$$

$$x(0)=\xi, \,\,\,t(0)= 0,\,\,\, u(0)=u_0(\xi)$$

Characteristic equations:

$$\frac{\mathrm{d}a}{\mathrm{d}\tau}=1, \,\,\,\frac{\mathrm{d}t}{\mathrm{d}\tau}=1, \,\,\,\frac{\mathrm{d}u}{\mathrm{d}\tau}=-\mu tu$$

Solving each of these ODE's in $\tau$ gives the following:

$$(1)\int \mathrm{d}a=\int \mathrm{d}\tau \,\,\,\,\,\,\,\,\,\,(2)\int \mathrm{d}t=\int \mathrm{d}\tau\,\,\,\,\,\,\,\,\,\,(3)\int \mathrm{d}u=-\int \mu tu\,\mathrm{d}\tau$$

$$a = \tau + F(\xi)\,\,\,\,\,\,\,\,\,\,t=\tau + F(\xi)$$

$$\therefore a=\tau + \xi \,\,\,\,\,\,\,\,\,\,\therefore t=\tau$$

$$\int \mathrm{d}u=-\int \mu \tau u\,\mathrm{d}\tau$$

$$\int \frac{1}{u}\,\mathrm{d}u=-\int \mu \tau \,\mathrm{d}\tau$$

$$\ln u = - \frac{1}{2}\mu \tau ^2+ F(\xi)$$

$$u = G(\xi)\,e^{-\frac{1}{2}\mu \tau^2}$$

$$\therefore u = u_0(\xi)\,e^{-\frac{1}{2}\mu \tau^2}$$

Substituting back the original coordinates we can re-write this expression with a coordinate change:

$$\xi = a-t \,\,\,\,\,\,\,\,\,\,\tau = t$$

$$\therefore u(a,t)=u_0(a-t)\,e^{-\frac{1}{2} t^2}$$

Now this is where I get stuck, how do I use the boundary data to come up with a well-posed solution?

$$u(0,t)=u_0(-t)\,e^{-\frac{1}{2}\mu t^2}=b\int_0^t u(a,t)\,\mathrm{d}a+b\int_t^\infty u(a,t)\,\mathrm{d}a$$

Very unsure how I can evaluate this integral...


$$u_a + u_t = -\mu t u$$ Charpit-Lagrange system of characteristic ODEs :

$$\frac{da}{1}=\frac{dt}{1}=\frac{du}{-\mu t u}$$ First characteristic equation, from $\frac{da}{1}=\frac{dt}{1}$ : $$a-t=c_1$$ Second characteristic equation, from $\frac{dt}{1}=\frac{du}{-\mu t u}$ : $$ue^{\mu t^2/2}=c_2$$ General solution of the PDE on the form of implicit equation $c_2=\Phi(c_1)$ : $$ue^{\mu t^2/2}=\Phi(a-t)$$ where $\Phi$ is an arbitrary function, to be determined according to a boundary condition. $$u(a,t)=e^{-\mu t^2/2}\Phi(a-t)$$

$$ $$ CONDITION : $u(a,0)=u_0(a)=e^{-\mu 0^2/2}\Phi(a-0)=\Phi(a)$

Now the function $\Phi(x)=u_0(x)$ is determined. We put it into the above general solution where $x=a-t$ : $$\boxed{u(a,t)=e^{-\mu t^2/2}u_0(a-t)}$$ The solution of the PDE fitting to the condition $u(a,0)=u_0(a)$ is fully determined if the function $u_0(a)$ is known. In this case the initial condition $u(0,t)=F(t)$ is superfluous. Moreover, this condition might introduce a contradiction with the condition $u(a,0)=u_0(a)$.

So, if the two conditions are specified without relationship between them, the problem has no solution in general.

The problem is likely to have a solution if the next relationship was satisfied :

$$u(0,t)=b\int_0^\infty u(a,t)\,\mathrm{d}a= e^{-\mu t^2/2}u_0(0-t)=e^{-\mu t^2/2}u_0(-t)$$ $$b\int_0^\infty e^{-\mu t^2/2}u_0(a-t)\,\mathrm{d}a=e^{-\mu t^2/2}u_0(-t)$$ $$b\int_0^\infty u_0(a-t)\,\mathrm{d}a=u_0(-t)$$

Conclusion :

If $u_0(a)$ is not a function of general form, but is a particular function which satisfies the equation $b\int_0^\infty u_0(a-t)\,\mathrm{d}a=u_0(-t)$ the problem has a solution which is : $u(a,t)=e^{-\mu t^2/2}u_0(a-t)$ .

  • $\begingroup$ Perfect. Is there any way I can solve that integral though? $\endgroup$ – Andrew Sullivan Mar 16 at 4:19
  • $\begingroup$ This is a very different mathematical problem that the problem raised in your question. This is an integral equation of this kind : Find all functions $y(x)$ such as $$b\int_0^\infty y(z+x)dz=y(x)$$ You should open another question specifically on this subject. Note that $y(x)=c\:e^{-bx}$ is a particular solution. $\endgroup$ – JJacquelin Mar 16 at 5:55

substitute $u(a,t)$ by $u_0(a-t)\exp(...)$ in the integral, and then you may find your way out.

  • $\begingroup$ By a change of variable, $y(x)=b\int_0^\infty y(z+x) dz=b\int_x^\infty y(z)dz$, and then this integral equation is in fact an ode. The solution proposed by JJacquelin is the only kind of solutions. $\endgroup$ – Bruno Apr 20 at 10:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.